Epidemiology, Prevention, and Public Health Management of Legionnaires’ Disease-An Updated Review for Healthcare Professionals. - Aldosari, Tuwayrish Fahad Tuwayrish Aldosari; Ghada Ebrahim Ali Mabouj; Abdulrahman Nada Alshamari; Ali Abdu Abbas Arishi,; Abdulaziz Mofareh Lagabi; Mousa Ahmed Ali Sahli; Ibrahim Hasen Qiraty; Areej Ahmed Alhamzi; Majed Mohammed Hasan Abukafitah; Asaad Masoud Hamad Darraj; et al. (Saudi Journal of Medicine and Public Health, 2025)
Background: Legionnaires’ disease (LD), a severe atypical pneumonia caused primarily by Legionella pneumophila, continues to pose significant public health challenges due to underdiagnosis, environmental persistence, and high morbidity and mortality. Aim: This review aims to provide healthcare professionals with an updated synthesis of the epidemiology, pathophysiology, clinical features, diagnosis, management, and prevention of LD. Methods: A comprehensive review of current literature and surveillance data was conducted, incorporating clinical, microbiological, and environmental findings related to LD presentations, diagnostic strategies, and therapeutic approaches. Results: Legionella species remain widely distributed in natural and man made water systems, with serogroup 1 of L. pneumophila responsible for most human infections LD often presents with fever, respiratory symptoms, and extrapulmonary manifestations such as gastrointestinal and neurological signs. Diagnosis requires a combination of urinary antigen testing, cultures, and imaging. Fluoroquinolones and macrolides represent first line therapy, with early treatment significantly improving outcomes Complications include respiratory failure, shock, renal injury, and multiorgan dysfunction, particularly in high risk populations Conclusion: Early recognition, targeted antimicrobial therapy, and robust water system management are crucial to reducing LD related morbidity and mortality.